Raising Awareness of the Impact of Stunting on Toddler Development Through Parental Education - Yanti, Eka Safitri; Imami, Retno; Arica, Arica (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
In 2023, the prevalence of stunting in Indonesia remains at 21.5%, showing only a marginal decrease of 0.1% from the previous year and still exceeding the WHO standard of 20%. Stunting adversely affects children, leading to impaired physical and cognitive development, increased risk of developmental disorders, and a higher likelihood of metabolic diseases in adulthood.This study utilized a multi-stage approach: data and area analysis, educational and developmental screening, and evaluation. Participants included 44 parents with their toddlers, 5 cadres, and 3 village officials. Knowledge among participants improved significantly, with 76% demonstrating enhanced understanding. Statistical analysis revealed a significant increase in knowledge post-intervention (p=0.000). Developmental assessments showed that 11% of toddlers were classified as "doubtful" and 23% as having "deviant" results. Parents of these children received education on age-appropriate stimulation, and cases were reported to local health workers. The goal is for the acquired knowledge to be widely applied, with ongoing routine screening for early detection and timely management of developmental issues.